Electrical tracking performance of LLDPE-natural rubber blends by employing combination of leakage current level and rate of carbon track propagation - Piah, M. A. M. (Institute of Electrical and Electronics Engineers, 2005)
Electrical tracking develops from surface discharge activity associated with the flow of leakage current on insulator surface under wet and contaminated conditions. Arcs created from this surface discharge phenomenon burn the polymer insulator material and create carbonized tracks in the long run. This paper reports on electrical tracking performance through the observation of leakage current and carbon track development of blends of linear low-density polyethylene with natural rubber (LLDPE/NR) either filled with or without alumina trihydrate. An electrical tracking and erosion test using the inclined-plane tracking method is conducted to study the overall performance of surface tracking properties. The combined effect of leakage current level and carbon track propagation rate is used as a new technique for describing the level of electrical tracking performance based on the proposed normalized degradation index. Morphological analysis is also carried out to investigate the surface microstructure before and after the tracking test. The experimental results show that different material compositions affect the leakage current and carbon track development. In addition, the calculated normalized degradation index has shown some correlation with the degree of surface deterioration.